APPLICATION OF INTEGRATED LEARNING STRATEGY OF PROFIT NETWORK IN INCREASING LEARNING OUTCOMES OF AL QUR'AN HADIS (Case Study of Class XI MAN IC Gowa) - Hasmirawati, Hasmirawati; Yaumi, Muhammad; Ahmad, La Ode Ismail (Jurnal Diskursus Islam, 2020)
The key issues examined are covering, how the implementation of an integrated learning strategy model Spider-webs on the subject Quran Hadis learners XI MAN IC Gowa, What the integrated learning strategy model of spider-webs can improve learning outcomes in Class X MAN IC Gowa students, and How to apply the integrated learning strategy of the Spider Web model in improving the learning outcomes of Class XI MAN IC Gowa. This research is a classroom action research conducted in the first semester of the academic year 2019-2020 consists of two cycles, each cycle consisting of 2 meetings. Furthermore, the data were analyzed qualitatively, which explains the results of actions during the teaching and learning process, and quantitatively calculated the data, namely the average score, frequency table, minimum value, maximum value, and percentage. The results showed that the integrated learning strategy of the spider-web model can improve student learning outcomes seen from an increase in the percentage of students’ mastery learning, from pre-cycle to cycle I, and to cycle II, namely 29 % pre- cycle there was an increase in cycle I, 82 % and cycle II reached 100 % and the average pre-cycle class was 67 an increase in cycle I to be 87 and in cycle II to 94.